2009
DOI: 10.1016/j.neuron.2008.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Coherence in the Perceptual Organization and Cortical Representation of Auditory Scenes

Abstract: Just as the visual system parses complex scenes into identifiable objects, the auditory system must organize sound elements scattered in frequency and time into coherent “streams”. Current neuro-computational theories of auditory streaming rely on tonotopic organization of the auditory system to explain the observation that sequential spectrally distant sound elements tend to form separate perceptual streams. Here, we show that spectral components that are well separated in frequency are no longer heard as sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
292
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 221 publications
(324 citation statements)
references
References 76 publications
31
292
1
Order By: Relevance
“…The responses studied here could supply the more abstract representation hypothesized by Averbeck and Romanski. What are the possible mechanisms underlying this transformation in the representation of sounds? Shamma and coworkers (35,39) suggested that some of these effects could be explained by depression of the thalamo-cortical synapse. Our results suggest that this process may actually occur earlier, because MGB neurons are also less informative about ST receptive fields but keep substantial information about auditory entities.…”
Section: Discussionmentioning
confidence: 99%
“…The responses studied here could supply the more abstract representation hypothesized by Averbeck and Romanski. What are the possible mechanisms underlying this transformation in the representation of sounds? Shamma and coworkers (35,39) suggested that some of these effects could be explained by depression of the thalamo-cortical synapse. Our results suggest that this process may actually occur earlier, because MGB neurons are also less informative about ST receptive fields but keep substantial information about auditory entities.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relative importance of these factors is still a matter of debate. In particular, while several psychophysical, neurophysiological, and modeling studies of auditory streaming performed during the last thirty years have focused on the importance of spectral-or tonotopic-contrasts for stream segregation (e.g., Hartmann and Johnson, 1991; for a review, see , recent work has emphasized the role of temporal coherence (Elhilali and Shamma, 2008;Elhilali et al, 2009; for a review, see . In this context, the notion of temporal coherence extends that of synchrony, and refers specifically to the repeated synchronous activation of auditory "channels" (or neural populations) tuned to different sound parameters, e.g., different frequencies, or different sound features, e.g., pitch and spatial location.…”
Section: Introductionmentioning
confidence: 99%
“…In such tasks, therefore, stream segregation impedes performance. A recent reurophysiological study of auditory streaming has taken advantage of this (Elhilali et al 2009). Conversely, several studies have found that listeners can more accurately recognize a familiar melody, that is temporally interleaved with another melody, if the two melodies form separate streams (Dowling 1973;Hartmann and Johnson 1991;McAdams 2002, 2003).…”
Section: Introductionmentioning
confidence: 99%